Aukštasis bibliotekininkystės mokslas Tarybų Lietuvoje - Sinkevičius, Klemensas (Knygotyra, 1970)
Attempts to organize higher library education in Lithuania were made long ago. An episodic course in bibliography was read in the old Vilnius University in 1829–1830, at Kaunas University in 1922 and 1925. After the restoration of Soviet power in Lithuania the Chair of bibliology was established at Vilnius State University on the 1st of September 1940, the course in bibliography was read. Lectures to start the preparation of skilled librarians and bibliographers was planned to read beginning from the autumn of 1941. The work was interrupted by the war and nazi occupation.The department of Librarianship was founded at Vilnius State University in 1949. During the last 20 years 590 specialists were trained in the full-time department and correspondence courses. They were appointed to work in different public, children, school, scientific, special and technical libraries, in scientific information offices. The staff of the Chair consists of 9 regular workers, 7 of them have scientific degrees and titles. The Chief of the Chair, docent L. Vladimirovas was elected, in competition, Director of the U. N. library in New York, in 1964.Recently the researches in quantitative and qualitative aspects were carried out, the aim of which was to ascertain Lithuania’s perspective needs in skilled library workers. As a result it was decided to elaborate a new curriculum and to specialize the training of librarians for public, scientific, technical, children and school libraries. Historical and philological subjects are preserved for the specialization of public, children and school libraries, for the specialization of technical libraries a technical-economical basis is given in the new curriculum.Proceeding from contemporary and perspective tasks of library work and information service, a number of new subjects is included into the curriculum: higher mathematics, computers and programming, applied linguistics, scientific information, etc.The new curriculum was approved on the 1st of August 1968.Consequently in 1969 the new name of Chair of Librarianship and Scientific Information was given to the Chair of Librarianship in the Vilnius V. Kapsukas State University in accordance with the new version of its work.